Interface Between Organizational Citizenship Behavior and Job Satisfaction Among a Slice of Health Professionals in an Egyptian Context - Abdel-Aziz, Basem Farouk (International Journal For Research In Health Sciences And Nursing, 2021)
Interface between Organizational Citizenship Behavior (OCB) and Job Satisfaction (JS) has been the focus of a horde of recent research. This relation could be found to be moderately positive, weakly positive, or non-demonstrable. However, the relation has never been reported to be a negative one. Valid and reliable measurement models of the two poles of the relationship were acquired from previous two observational cross-sectional studies concurrently conducted by the researcher on a slice of healthcare professionals conducting their graduate studies in High Institute of Public Health, Alexandria University, Egypt. Four consecutive samples (S1, S2, S3, & S4) were collected one month apart. Studying the postulated relationship progressed in three phases, the first phase probed a hypothesized non-directional correlation, the second phase investigated a hypothesized structural directional influence from OCB to JS and the third phase examined a hypothesized structural directional influence from JS to OCB. Study models were examined using structural equation modeling (SEM) using unweighted least squares estimators and suitable global and local fit indices. The three models displayed a positive weak significant relationship between OCB and JS. Multiple group analysis generally revealed weak invariance across time, and participants' personal characteristics. Recommendations, managerial implications, future research directions, and limitations have been underscored.